2011
DOI: 10.1097/opx.0b013e318230f03a
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Developmental Eye Movement Test

Abstract: Although the DEM is widely used in optometric practice, the results of this study suggest that clinicians should be cautious about using the DEM test in isolation for reaching a diagnosis or monitoring the effectiveness of treatment for saccadic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 5 publications
1
30
1
Order By: Relevance
“…While other studies have reported significant relationships between the DEM ratio and reading outcomes, they also noted that the associations were stronger for the horizontal and vertical times. Furthermore, the horizontal and vertical DEM times have shown better repeatability than the ratio, which may explain their stronger associations with academic outcomes in the present study.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…While other studies have reported significant relationships between the DEM ratio and reading outcomes, they also noted that the associations were stronger for the horizontal and vertical times. Furthermore, the horizontal and vertical DEM times have shown better repeatability than the ratio, which may explain their stronger associations with academic outcomes in the present study.…”
Section: Discussionmentioning
confidence: 55%
“…43 While other studies have reported significant relationships between the DEM ratio and reading outcomes, 36,39 they also noted that the associations were stronger for the horizontal and vertical times. Furthermore, the horizontal and vertical DEM times have shown better repeatability than the ratio, 44 which may explain their stronger associations with academic outcomes in the present study. Importantly, while our findings demonstrate that slower horizontal and vertical DEM times are associated with lower levels of academic performance (including reading and other core academic skills) we cannot conclude a causative relationship, given the cross-sectional nature of this study.…”
Section: Discussionmentioning
confidence: 56%
“… Orlansky et al (2011) performed a more extensive evaluation of reliability in a multi-center study. More than 180 subjects were tested in two sessions, in each of which they were each evaluated three times.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this concept was better explained by the agreement term, which represents the similarity of scores, and judgment or diagnoses with respect to the degree in which they differ ( Kottner and Streiner, 2011 ). Rouse et al (2004) and Orlansky et al (2011) have shown that the true problem with the DEM test appears to be the improvement between sessions, which can be defined as a form of lack of agreement. This improvement was also defined as learning effect ( Orlansky et al, 2011 ) and reported in terms of mean change and its respective limits of agreement ( Altman and Bland, 1983 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation